SPECKLE-TRACKING INTRACARDIAC ECHOCARDIOGRAPHY IN ATRIAL FIBRILLATION PATIENTS DURING RADIOFREQUENCY ISOLATION OF PULMONARY VEINS - A. V. Smorgon; D. I. Lebedev; S. Yu. Usenkov; A. A. Dubanaev; E. A. Archakov; R. E. Batalov; A. E. helemekhov; S. V. Popov (Российский кардиологический журнал, 2017)
Aim. To evaluate the speckle-tracking echocardiography (STE) application in atrial fibrillation (AF) patients during catheter treatment, by the data from intracardiac echocardiography (ICE).Material and methods. Totally, 30 patients included, with persistent and paroxysmal AF. In 25 (84%) the main disease was arterial hypertension, of those 14 (46%) had hypertension together with coronary heart disease. In 16% cases (4 patients) AF was idiopathic. All patients had indications for catheter treatment of the arrhythmia.Results. Before the start of radiofrequency intervention (RFI), superior pulmonary vein (PV) deformation was 24,5±1,5%, after the intervention 17,5±1,1%, tissue deformation decreased by 7% (р<0,001); of the left inferior PV before RFI — 21,5±0,9%, after — 14,4±0,9%, tissue deformation decreased by 7,1% (р<0,001); right inferior PV before RFI — 21,2±1,3%, after — 14,9±1,1%, tissue deformation decreased by 6,2% (р<0,001); right inferior before RFI — 20,5±1,1%, after — 14,4±1,1%, deformation change 6,1% (р<0,001). Under the influence of RFI, velocity of upper PV deformation decreased by 8,1% (р<0,001),  to -5,36±0,5%, after — 4,93±0,35%; in lower inferior PV decrease of velocity by 8,3% (р<0,001), before RFI -5,38±0,6%, after — 4,93±0,55%; right superior PV — decrease of PV deformation by 8,5% (р<0,001),  before RFI -5,5±0,15%, after -5,0±0,33%; in right inferior 8,2% (р<0,001) before RFI -5,9±0,4%, after -5,4±0,4%.Conclusion. Decrease of deformation by more than 6% and velocity of deformation by 8% after radiofrequency intervention are relevant signs of pulmonary veins ostia isolation.